Determinan Faktor yang Berkontribusi terhadap Kejadian Stunting pada Balita di Wilayah Kerja Puskesmas Langara Kabupaten Konawe Kepulauan - Harleli Harleli (Yayasan Literasi Sains Indonesia, 2026)
Stunting is a chronic nutritional problem among children under five. The assessment of stunting status is conducted using the height-for-age (HFA) index based on z-scores, where a value of < −2 standard deviations indicates stunting. This study aimed to identify determinant factors contributing to stunting among children aged 12–59 months in the working area of Langara Public Health Center. This study employed a quantitative approach with an analytical cross-sectional design. The sample consisted of 100 children under five selected using simple random sampling. The inclusion criteria were children aged 12–59 months at the time of the study. Data were collected through observation and interviews using questionnaires on respondent characteristics, complementary feeding (MP-ASI) history, and family income. Data analysis was conducted bivariately using the Chi-Square test with a significance level of α = 0.05. The bivariate analysis results showed a significant association between complementary feeding history (p = 0.003), while family income showed no significant association (p = 0.223) with the incidence of stunting among children aged 12–59 months in the working area of Langara Public Health Center.